2002
DOI: 10.1037/0894-4105.16.1.15
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of short- and long-term outcomes after traumatic brain injury in children: Behavior and achievement.

Abstract: Longitudinal behavior and achievement outcomes of traumatic brain injury (TBI) were investigated in 53 children with severe TBI, 56 children with moderate TBI, and 80 children with orthopedic injuries not involving brain insult. Measures of preinjury child and family status and of postinjury achievement skills were administered shortly after injury. Assessments were repeated 3 times across a mean follow-up interval of 4 years. Results from mixed model analysis revealed persisting sequelae of TBI. Recovery of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
321
12
8

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 360 publications
(374 citation statements)
references
References 81 publications
33
321
12
8
Order By: Relevance
“…Research is emerging that the main predictor for a good outcome may not be the injury itself but rather the child's environment following such injury. (29) Similar to the finding those premorbid behavioral and personality disturbances are predictive of similar problems after the injury; family discord prior to an injury is highly predictive of divorce, social isolation, and substance abuse following the TBI. (30) It has been suggested that there are two burdens that families experience during the recovery of their child which are objective and subjective.…”
Section: Interventionssupporting
confidence: 57%
“…Research is emerging that the main predictor for a good outcome may not be the injury itself but rather the child's environment following such injury. (29) Similar to the finding those premorbid behavioral and personality disturbances are predictive of similar problems after the injury; family discord prior to an injury is highly predictive of divorce, social isolation, and substance abuse following the TBI. (30) It has been suggested that there are two burdens that families experience during the recovery of their child which are objective and subjective.…”
Section: Interventionssupporting
confidence: 57%
“…Consistent with this interpretation, deficits in self-awareness are common sequelae of severe TBI. 50 An important clinical implication of the difference between self-and parent reports, and of the discrepancy between adolescent self-report and documented deficits in long-term outcomes 51 is that adolescents are either unaware of their limitations or unwilling to admit to them. Such lack of insight or denial may affect adolescent compliance with recommendations for services that parents or professionals deem necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric traumatic brain injury (TBI) results in substantial neurobehavioral morbidity for survivors, including persistent impairments in emotional, social, behavioral, and neuropsychological functioning that persist well beyond the acute phase of injury (e.g., Anderson et al, 2001Anderson et al, , 2006Taylor et al, 2002;Yeates et al, 2005). A clear relationship has been observed for physical and cognitive outcomes in TBI, with the severity of TBI contributing to greater impairment .…”
Section: Introductionmentioning
confidence: 99%